The Power of Inclusivity in Branding: A Systematic Literature Review on Trends, Theoretical Perspectives, and Research Landscape - Purnomo, Fajrin; Putri, Nadia Ramadhani Nugroho; Rodhiyana, Rosda; Hartini, Sri; Rachmanu, Edvian Ditya (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to explore the role of inclusivity in brand strategy through a Systematic Literature Review (SLR) of 21 peer-reviewed articles indexed in the Scopus database. The articles were analyzed based on research trends, theoretical frameworks, methodological approaches, publication outlets, and geographical distribution. The findings indicate a significant increase in academic attention to brand inclusivity beginning in 2022, with a peak in 2024. The reviewed studies applied various theoretical perspectives, including Transformative Service Research, Social Identity Theory, Moral Foundations Theory, and the Technology Acceptance Model, reflecting conceptual diversity in examining inclusive branding. Methodologically, qualitative approaches, particularly case studies, are the most dominant, followed by experiments, surveys, and mixed methods. Most articles were published in high-ranking journals (Q1 and Q2), suggesting strong academic interest and relevance. Geographically, the majority of studies focused on developed countries, especially the United States and the United Kingdom. A key limitation is the exclusive use of the Scopus database, which may affect generalizability. Future research is encouraged to diversify data sources and methodological approaches.